Respuesta :
Answer:
y/2
Step-by-step explanation:
First, multiply 6 on both sides. 2x+6 = 3y+6. Subtract both sides by 6.
2x = 3y. 2x is 6*x/3. So ^*x/3 = 3y. Divide both sides by 6 and x/3 = 3y/6.
3y/6 = y/2.
ANSWER
[tex] \frac{x}{3} = \frac{y}{2} [/tex]
EXPLANATION
Given:
[tex] \frac{x + 3}{3} = \frac{y + 2}{2} [/tex]
Split the numerator on both sides of the equation to get:
[tex]\frac{x }{3} + \frac{3}{3} = \frac{y}{2} + \frac{2}{2} [/tex]
[tex]\frac{x }{3} + 1 = \frac{y}{2} + 1[/tex]
Solve for [tex] \frac{x}{3} [/tex]
[tex]\frac{x }{3} = \frac{y }{2} + 1 - 1 [/tex]
Simplify:
[tex]\frac{x }{3} = \frac{y}{2}[/tex]
[tex] \frac{x}{3} = \frac{y}{2} [/tex]
EXPLANATION
Given:
[tex] \frac{x + 3}{3} = \frac{y + 2}{2} [/tex]
Split the numerator on both sides of the equation to get:
[tex]\frac{x }{3} + \frac{3}{3} = \frac{y}{2} + \frac{2}{2} [/tex]
[tex]\frac{x }{3} + 1 = \frac{y}{2} + 1[/tex]
Solve for [tex] \frac{x}{3} [/tex]
[tex]\frac{x }{3} = \frac{y }{2} + 1 - 1 [/tex]
Simplify:
[tex]\frac{x }{3} = \frac{y}{2}[/tex]